2016
DOI: 10.4236/oalib.1102145
|View full text |Cite
|
Sign up to set email alerts
|

Survival Outcomes of Breast Cancer in Ghana: An Analysis of Clinicopathological Features

Abstract: Breast cancer is the most frequently diagnosed cancer and the leading cause of cancer death in female's worldwide. Its incidence is on the ascendancy in Africa including Ghana. In addition, Ghanaian women are more likely to be diagnosed with high-grade tumours that are triple negative breast tumours. The objectives of the study were to investigate the clinicopathologic features of breast cancer in Ghanaian women; identify and describe breast cancer survival pattern in Ghana and factors that explain the dispari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 22 publications
14
39
0
Order By: Relevance
“…In this 6-year retrospective follow up study, the overall survival rates at 1, 3, and 5 years were, 97.2%, 80.8%, and 46.2% respectively. This finding is consistent with other previous studies which have been conducted in Malaysia (70.8%, 56.9% and 49.4%) (23) and Ghana, (47.9%) (17) .However, this finding is higher than those in other African countries in Tanzania (21.8%) (24) and Cameroon (30%) (25) at 5 years and even lower than previous results in Uganda (51.8 %) (26), and Vietnam, (94%, 83% and 74%)(4).This ,figure is still lower when compared with that of studies of high income countries such as Northwest Iran (96%, 86%, and 81%), Germany( 83% ),and the Qidong(83.61%,67.53%,and58.75%)respectively (27)(28)(29).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In this 6-year retrospective follow up study, the overall survival rates at 1, 3, and 5 years were, 97.2%, 80.8%, and 46.2% respectively. This finding is consistent with other previous studies which have been conducted in Malaysia (70.8%, 56.9% and 49.4%) (23) and Ghana, (47.9%) (17) .However, this finding is higher than those in other African countries in Tanzania (21.8%) (24) and Cameroon (30%) (25) at 5 years and even lower than previous results in Uganda (51.8 %) (26), and Vietnam, (94%, 83% and 74%)(4).This ,figure is still lower when compared with that of studies of high income countries such as Northwest Iran (96%, 86%, and 81%), Germany( 83% ),and the Qidong(83.61%,67.53%,and58.75%)respectively (27)(28)(29).…”
Section: Discussionsupporting
confidence: 94%
“…This finding is in agreement with different studies conducted in African countries (17,32) ,and also in the study done in Iran (33) ,in which lymph node status was an important determinant of survival. Despite being positive lymph node status, as the number of involved lymph nodes increases, so does the relapse rate, while the survival rate decreases.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consequently, survival among African women with breast cancer is much lower compared to that of Whites, with as low as 13.6% in Gambia [20]. In line with the lower rates particularly in sub-Saharan Africa, a recent study on survival outcomes of breast cancer in Ghana demonstrated that the overall 5-year survival was 47.9% [21].…”
Section: Introductionmentioning
confidence: 99%